2009
DOI: 10.1177/1524838009349517
|View full text |Cite
|
Sign up to set email alerts
|

Matricide: A Critique of the Literature

Abstract: Matricide, the killing of mothers by their biological children, is a very rare event, comprising less that 2% of all U.S. homicides in which the victim-offender relationship is known. This manuscript examines more than 20 years of U.S. homicides to determine the age and gender characteristics of matricide offenders. These data reveal that most mothers are killed by their adult sons. Daughters younger than 18 years are the most infrequent killers of mothers. This article examines the incidence of parricide, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 63 publications
2
43
0
1
Order By: Relevance
“…5 This was presented as an alternative to early psychoanalytic thinking that hatred of the mother was a derivative of the oedipal complex.5 Most of the available studies have examined schizophrenic sons who killed their mothers 6,7,8 with very few mentioning maternal homicide by daughters. 9,11 In this report, we have presented a schizophrenic son and daughter who killed their mothers. Both of them were not close to their mothers yet they lived with them and were dependent on them.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…5 This was presented as an alternative to early psychoanalytic thinking that hatred of the mother was a derivative of the oedipal complex.5 Most of the available studies have examined schizophrenic sons who killed their mothers 6,7,8 with very few mentioning maternal homicide by daughters. 9,11 In this report, we have presented a schizophrenic son and daughter who killed their mothers. Both of them were not close to their mothers yet they lived with them and were dependent on them.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies have shown an ambivalent relationship between schizophrenic sons and their mothers whom they had killed. 7,9,11 Singal & Dutta 7 indicate that there is intense, conflict-laden relationship between schizophrenic sons and their mothers. The majority of the patients that they studied described their mothers as being domineering and demanding on one hand but tolerant and affectionate on the other hand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O matricídio é definido como o assassinato da mãe por um filho e é uma das formas mais raras de homicídio 14 . 16 . A relação do transtorno mental com o matricídio é bastante complexa e ainda pouco clara nos poucos casos descritos na literatura 17 .…”
unclassified